AN ANALYSIS OF SERVICE QUALITY ON VSAT NETWORK USING WIRESHARK - Abdilah Yusuf; Khairil Khairil; Eko Prasetiyo Rohmawan (UNIVED Press, 2024)
The need for the internet nowadays is very high, because students and office employees have to carry out all activities using the internet. This causes an increase in connection traffic on the internet and workload on internet service provider servers. Especially in areas where it is still difficult to access the internet network. VSAT is one of the recommended internet access media because it can be installed and accessed even in remote areas. For this reason, it is hoped that an agency or company will implement and monitor the service quality on VSAT network system so that the data flow or data traffic within the network is at the quality of service level. Analyze network feasibility or quality of service to determine the value of several segments such as jitter, packet loss, delay, throughput using Wireshark software. The result shows that it has succeeded in analyzing network feasibility on VSAT network media using Wireshark software. In implementing Wireshark software to network feasibility testing, it can be concluded that VSAT network is very suitable to be implemented at SD 65. Then, the results of this network feasibility measurement will also be useful to help the maintenance or repair process easier, because it will provide useful data for technicians to diagnose conditions on VSAT.